Reversal of dabigatran anticoagulation ex vivo: Porcine study comparing prothrombin complex concentrates and idarucizumab - Honickel, Markus; Treutler, Stefanie; Ryn, Joanne van; Tillmann, Sabine; Rossaint, Rolf; Grottke, Oliver (Thrombosis and Haemostasis, 2015)
Urgent surgery or life-threatening bleeding requires prompt reversal of the anticoagulant effects of dabigatran. This study assessed the ability of three- and four-factor prothrombin complex concentrate (PCC) and idarucizumab (specific antidote for dabigatran) to reverse the anticoagulant effects of dabigatran in a porcine model of trauma. Twelve animals were given dabigatran etexilate (DE) orally and dabigatran intravenously, before infliction of trauma. Six animals received tranexamic acid plus fibrinogen concentrate 12 minutes post-injury. Six PCCs (each 30 and 60 U/kg) and idarucizumab (30 and 60 mg/kg) were added to blood samples ex vivo. Coagulation was assessed by several coagulation assays. All coagulation parameters were altered after dabigatran infusion (plasma level: 442 ± 138 ng/ml). Both threeand four-factor PCCs mostly or completely reversed the effects of dabigatran on thromboelastometry variables and PT but not on aPTT. Idarucizumab neutralised plasma concentrations of dabigatran, and reversed the effects of the drug on coagulation variables. Thrombin generation showed dose-dependent over-correction following the addition of PCC, implying that elevated levels of thrombin are required to overcome dabigatran-induced coagulopathy. In contrast, treatment with idarucizumab returned thrombin generation to baseline levels. Following trauma, therapy with tranexamic acid plus fibrinogen improved correction of coagulation parameters by PCC, and thromboelastometry parameters by idarucizumab. All investigated PCCs improved dabigatran- and trauma-induced coagulopathy to a similar degree. In conclusion, this study shows that three- and four-factor PCCs are similarly effective for dabigatran reversal. Idarucizumab also reversed the effects of dabigatran and, unlike PCCs, was not associated with over-correction of thrombin generation.Note: This study was performed at the RWTH Aachen University Hospital, Pauwelsstrasse 30, D-52074 Aachen, Germany.
Keywords: Dabigatran; idarucizumab; prothrombin complex concentrate; trauma; thrombin generation